Analysis of the Influence of Education on Productivity and Economic Growth - Adimas Rois Adnan; Roma Nova Cahjati Poetry (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2026)
Education plays a strategic role in improving labor productivity and promoting sustainable economic growth, particularly in developing countries such as Indonesia. However, despite continuous government investment in the education sector, Indonesia still faces challenges related to educational quality, labor productivity, and regional economic disparities. This study aims to analyze the effect of education on labor productivity and economic growth in Indonesia and to examine the mediating role of productivity in the relationship between education and economic growth. This study employs a quantitative approach using panel data from 34 Indonesian provinces during the 2020–2024 period. Data were obtained from the Central Statistics Agency (BPS), the Ministry of Manpower, and other official publications. Panel data regression analysis using the Fixed Effect Model was applied to estimate the relationships among the variables. The findings reveal that education, measured by average years of schooling, has a positive and significant effect on labor productivity and economic growth. Each additional year of schooling significantly increases worker productivity and contributes to regional economic growth. Furthermore, labor productivity significantly mediates the relationship between education and economic growth. The study concludes that improving educational quality and accessibility is essential for strengthening labor productivity and accelerating sustainable economic development in Indonesia.